Ideology, Politics and Society in Antonio Gramsci's Theory of Hegemony - Leśniak, Tomasz (Hybris, 2012)
In this article, I examine Antonio Gramsci's theory of hegemony by situating it in relation to a more general intellectual and socio-political context involving orthodox Marxism, October Revolution and Italian fascism. I first briefly outline the problem of economism in Marxist theory, as it is the main object of Gramsci's critique developed fully in the Prison Notebooks. The next two sections are devoted to October Revolution and Italian fascism, interpreted as two elements of the socio-political conjuncture which called into question Marx's 'base/superstructure' model of society and its mechanistic rearticulation. Finally, I discuss Gramsci's mature political theory as an attempt to break with economic determinism and class reductionism of classical and orthodox Marxist theory. I argue that his original conception of hegemony constitutes an advance towards a non-essentialist and relational conception of politics and society.